2009
DOI: 10.1007/s11306-009-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics as a potentially novel diagnostic and stratification tool for knee osteoarthritis

Abstract: Metabolomics has been used as a tool in disease diagnosis and phenotype prediction. A urinary metabolomic study based on GC-MS in combination with multivariate statistics was used here to classify between knee osteoarthritis (OA) and healthy controls. OPLS-DA of the spectral data showed distinct metabolic profile variations between OA patients and healthy controls and between two OA phenotypes. Differential metabolites reveal up-regulated TCA cycle associated with OA and histamine metabolism disorders accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…All prior metabolomic studies in humans have been cross-sectional in nature comparing individuals with or without OA using either urine 18, 40 , serum 19 , synovial fluid 41 or plasma 20 . An NMR-based urine metabolomics study that used samples from the Johnston County Osteoarthritis project found differences in participants with radiographic hip or knee OA from controls and noted a correlation of a metabolite profile with radiographic OA severity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…All prior metabolomic studies in humans have been cross-sectional in nature comparing individuals with or without OA using either urine 18, 40 , serum 19 , synovial fluid 41 or plasma 20 . An NMR-based urine metabolomics study that used samples from the Johnston County Osteoarthritis project found differences in participants with radiographic hip or knee OA from controls and noted a correlation of a metabolite profile with radiographic OA severity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, metabolomics has found applications in many chronic metabolic disorders, such as diabetes, lung disease, neurodegenerative disease, cancer, hypertension, and cardiovascular diseases [3,4,5]. In recent years, metabolomics have gained popularity in the orthopedic field, including osteonecrosis, osteoarthritis, ankylosing spondylitis, bone tumors and osteoporosis [6,7,8,9]. However, the application of metabolomics in osteoporosis has just begun.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the use of mass spectrometry-based (MS-based) metabolomics as a reliable tool for detecting biomarker patterns for the purpose of finding differences among samples. This information has proven effective for disease diagnosis (Cortes et al 2010;Li et al 2010;Pasikanti et al 2010).…”
Section: Introductionmentioning
confidence: 99%